Dylematy nauczania etyki w środowisku szkolnym - Grzegorz Stolarski (Studia Ecologiae et Bioethicae)
This essay is an metaethical reflection on the character of teaching ethics in school and academic realities of Poland, the aim is to show the type of ethics which is the best in achieving the syllabus and educational assumptions of the discipline. It seems that the most important of them are the following issues: - Rationalization of ethical choices, i.e. giving the reasons for choosing particular moral values - the clearly presented problem of the responsibility for the decisions - Strengthening proper improvements of the character, which enable to choose and defend moral values: tolerance, ecological responsibility. There are two the most general ways distinguished of presentation of ethics within school or academic lecture: the “naturalistic” and the “engaged” one. The naturalistic approach is restricted to the presentation of various ethical systems without any discussion included on evaluating these systems, the engaged approach critically analyses different ethical solutions, reasonably assessing their character. Despite the arguments for the naturalistic approach (presently fashionable criticism of ethics, the issue of toleration and avoidance of the idéologisation) I undertake to defend the engaged approach as better at giving possibilities of reasonable criticism of moral behaviors and as the result of this criticism, moral attitudes which are the goal of teaching ethics in school.